THE LANGUAGE OF MEDICAL ADVERTISING MATERIALS - Birutė Briaukienė (Respectus Philologicus, 2015)
Increasingly audacious steps in advertising are made to affect the customer and to encourage them to buy the advertised goods. Advertising is highly important in gaining a foothold in the business environment. Usually, the advertising texts fail to meet the norms of the standard Lithuanian language. The aim of this article is to compare the language of the advertising booklets of two pharmacies.